ETHNO-RELIGIOUS AND POLITICAL DYNAMICS IN THE APPLICATION OF REFUGEE LAWS - Lawal , Olawale Iskil (IJRDO - Journal of Social Science and Humanities Research, 2023)
Since its emergence in international law, the United Nations Organization’s 1951 Convention Governing Refugee Status (hereafter refers to as 1951 Geneva Convention) has acted as type genus of the international protection law because it is the earliest document which defines and describes refugee in pure legal environment. The refugee is a legal concept in international law, where states are enjoined to comply with certain obligations, but it was established under strong humanitarian principle. Its legality, however, does not dimmish states’ right to sovereignty and protection of territorial integrity.  Notwithstanding, states have often found relief or escape from the obligations of international protection law especially when local dynamics prevent wholesome adherence to the principles of international protection law. It is common place to witness the interference of religion, politics, sectarianism et al, in refugee asylum administrations. This work highlights some of these instances with the hope that subsequent studies will sniff out more areas of these dynamics.